Aurelia aurita jellyfish collagen: Recovery properties - Noora Barzkar; Stanislav A. Sukhikh; Anastasiia V. Zhikhrev; Elizaveta Yu. Cheliubeeva; Anastasia I. Kapitunova; Danil I. Malkov; Olga O. Babich; Yuliya V. Kulikova (Foods and Raw Materials, 2025)
Wound and burn healing is a complex physiological process that can be facilitated by medications based on marine collagen. In this regard, biomass of the Aurelia aurita jellyfish is a promising alternative source of medical collagen. As the global incidence of burns and wounds continues to grow, new healing methods have become a relevant area of medical science. This study featured acetic acid as a means of marine collagen extraction from A. aurita biomass. The physical and chemical properties of jellyfish collagen were determined gravimetrically and included such indicators as water solubility and water holding capacity. The molecular weight was defined by gel electrophoresis. The spectral studies relied on the method of UV spectroscopy. The regenerative experiments included such parameters as cytotoxicity, antioxidant properties, adhesion, and wound healing rate, as well as a quantitative PCR analysis. The optimal conditions for maximal collagen yield were as follows: 0.5 M acetic acid and 48 h extraction time. However, the collagen yield was very low (≤ 0.0185%). The high water holding capacity showed good prospects for A. aurita collagen to be used as hemostatic sponge. The acid-soluble collagen sample had a molecular weight of 100–115 kDa, which made it possible to classify it as type I. A. aurita jellyfish collagen revealed no cytotoxic properties; it had no effect on adhesion, migration, and proliferation of keratinocytes, neither did it affect the expression of cell differentiation markers. The wound healing model proved that the marine collagen had regenerative properties as it was able to increase the wound healing rate by 24.5%. Therefore, collagen extracted from the biomass of A. aurita jellyfish demonstrated good prospects for cosmetology and regenerative medicine.